Eksekusi Terhadap Pembatalan Surat Izin Mendirikan Bangunan Pada Perkara Tata Usaha Negara - Zainuddin Zainuddin (DE LEGA LATA: JURNAL ILMU HUKUM, 2019)
State and Government administrative decisions, namely decisions made by Government Agencies, both regulating and statutory (beschikking). Making provisions is a legal act. As a legal act the provision gives birth to rights and / or obligations, and the provisions that give birth to rights and / or obligations are called positive terms. This research is categorized in normative type research, where the data sources used are secondary data sources with data obtained through library research (library research) by processing qualitative data analysis. the focus of the problem in this study is how the execution of the cancellation of the building permit letter in the state administration case.